Molecular signatures in exosomes as diagnostic markers for neurodegenerative disorders - Palaniswamy Rani; Sevugan Karthik; Sampathkumar Srisharnitha A (Annals of Alzheimer's and Dementia Care - Peertechz Publications, 2020)
Exosomes are small membrane-bound entities of endocytic origin. These membrane-derived, extracellular vesicles have been shown to be secreted by a number of cell types such as adipocytes, platelets, cardiac progenitor cells, muscle cells, mesenchymal stem cells, lymphocytes, tumor cells, embryonic stem cells, umbilical cord blood-derived cells and cells in the central nervous system including neurons, neuroglial cells etc., These extracellular vesicles contain various protein, lipid, pro-inflammatory cytokines and RNA species whose content is altered under pathological diseased conditions of the CNS. Currently, the techniques available to diagnose neurodegenerative disorders involve analysing the physiological levels of certain proteins in the Cerebrospinal Fluid (CSF) and checking for extracellular senile plaque formation (protein aggregation and accumulation) in the brain using MRI/CT scans. These techniques are quite expensive, invasive and painful in nature as collecting the CSF and accessing the brain area are difficult. In the past few years, there is a growing interest on using exosomes for diagnosis of neurodegenerative disorders due to their easy availability from most of the biological fluids including the blood, urine, saliva, breast milk, semen etc., their extremely high disease-specific bio-molecular signature/profile, the ability of exosomes to cargo a variety of biomolecules in between cells and their capacity to cross the blood-brain barrier. These make them a potential biomarker for neurodegenerative disorder. This review begins with a brief introduction about exosomes and focuses mainly on using exosomes for diagnosing major neurodegenerative diseases like Prion disease, Amyotrophic lateral sclerosis, Huntington's disease, Parkinson's disease, and Alzheimer's disease.